Comparison of national extension systems: Application of the best-fit framework - Davis, Kristin E. (International Food Policy Research Institute, 2020)
As seen in Chapter 2, extension has evolved over the decades in various ways: in terms of its governance structure, in terms of who provides extension, in terms of capacity (staffing) and management, and in terms of advisory methods. However, the analysis in Chapter 2 was centered on the global level, focusing on the big picture and trends over time. This did not include more detailed assessments of national and regional extension systems using the best-fit characteristics. This chapter offers a synthesis of information from in-depth country and regional assessments that were conducted mainly since 2015. These assessments took place with various partners and projects. To pull out comparisons of the national systems, this chapter applies the best-fit approach (see Chapter 1). Note that this level of analysis still does not look at the performance or the impact of extension services (Chapters 4–8 cover performance assessment issues). Rather, this chapter presents a snapshot of extension services zooming in at the country or regional level.